2021
DOI: 10.1021/acs.jpcb.1c03245
|View full text |Cite
|
Sign up to set email alerts
|

Protein Stability Depends Critically on the Surface Hydrogen-Bonding Network: A Case Study of Bid Protein

Abstract: Understanding how proteins retain structural stability is not only of fundamental importance in biophysics but also critical to industrial production of antibodies and vaccines. Protein stability is known to depend mainly on two effects: internal hydrophobicity and H-bonding between the protein surface and solvent. A challenging task is to identify their individual contributions to a protein. Here, we investigate the structural stability of the apoptotic Bid protein in solutions containing various concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…However, the crystal structures of QTY proteins need to be determined to support the hypothesis. In contrast, a more recent publication showed that the soluble BH3 interacting-domain death agonist protein with similar QTY substitutions at the core region resulted in mutations with comparable secondary structures but was more prone to chemical denaturation only when surface hydrogen bond interactions were negated by a high concentration guanidine hydrochloride …”
Section: Novel Structures Assembly and Interaction Designsmentioning
confidence: 99%
“…However, the crystal structures of QTY proteins need to be determined to support the hypothesis. In contrast, a more recent publication showed that the soluble BH3 interacting-domain death agonist protein with similar QTY substitutions at the core region resulted in mutations with comparable secondary structures but was more prone to chemical denaturation only when surface hydrogen bond interactions were negated by a high concentration guanidine hydrochloride …”
Section: Novel Structures Assembly and Interaction Designsmentioning
confidence: 99%
“…The BH3 interacting-domain death agonist (Bid) protein (22 kDa; Figure S3A) is used as a model protein in the present work. , Wild-type (WT) Bid in a regular buffer is folded below water’s freezing point. It was recently reported that WT Bid (hereafter abbreviated only as Bid) in a 3 M guanidinium hydrochloride (GdnHCl) solution can undergo reversible cold and heat denaturation above water’s freezing temperature; it is largely unfolded at temperatures below 280 K or greater than 330 K in 3 M GdnHCl. In a 1 M GdnHCl solution, Bid is largely unfolded at temperatures below 250 K or greater than 350 K .…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported 18 that WT Bid (hereafter abbreviated only as Bid) in a 3 M guanidinium hydrochloride (GdnHCl) solution can undergo reversible cold and heat denaturation above water's freezing temperature; it is largely unfolded at temperatures below 280 K or greater than 330 K in 3 M GdnHCl. In a 1 M GdnHCl solution, Bid is largely unfolded at temperatures below 250 K or greater than 350 K. 18 We performed CD measurements on Bid in 0 and 3 M GdnHCl solutions at varying temperatures (Figure 2A,B). Consistent with the literature, 18 we found that Bid in 0 M GdnHCl manifests only heat denaturation (>360 K), whereas Bid in 3 M GdnHCl shows both cold and heat denaturation above water's freezing temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations